(untitled) (Islamic Sciences Journal, 2023)
Praise is to Allah Almighty, Lord of the worlds, and the blessings and peace of Allah Almighty is upon our Prophet Muhammad and his family and companions. My research is titled (The opinion of al-Kamal ibn al-Hamam (D. 861 AH) in Mental Approval and Disapproval - a comparative study-) in which I dealt with the personal opinions from the doctrinal aspect, and I found that it expanded in the narration of opinions with invoking evidence from the Holy Qur’an and the purified Sunnah of the Prophet, and sometimes evidence from Reason and discuss its opponents in all scientific ways and put examples for clarification, giving preference to what he deems appropriate. Kamal bin al-Hamam - may Allah Almighty have mercy on him - has proven the issue of mental Approval and Disapproval, and that they are understood by reason, that intellect according to Kamal bin al-Hamam - may Allah Almighty have mercy on him - is the basis of knowledge.